Nilai-nilai kebajikan: Kebaikan hati, loyalitas, dan kesalehan dalam konteks Budaya Melayu - Dede Fitriana Anatassia; Mira Noor Milla; Subhan El Hafiz (Jurnal Psikologi Ulayat, 2015)
The belief in good values that live in the community have an influence on the individual’s behavior. Virtue is one of them. Virtues found to have links with the individual’s character and personality. By using the approach of constructive realism indigenous psychology, this study aims to explore the virtues in the context of Melayu culture. Data collection techniques in this study were open ended questions and multiple responses. Data were analyzed with qualitative and quantitative methods using NVivo. It was found that kindness and loyalty are the core virtues that are considered important in everyday life. In the relationship context, the behaviors target of these values is higher in the community than personal. Virtues was found to be differ according to the demands of the situation. These virtues shifted in problem solving situations, where kindness and empathy are expected to appear less than serenity and resourceful. It is clear that the virtues which embraced by the individual does not always manifest if the situation is not supportive for the emergence of these virtues.